The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1111/j.1364-3703.2009.00571.x
|View full text |Cite
|
Sign up to set email alerts
|

Expression and regulation of Sclerotinia sclerotiorum necrosis and ethylene‐inducing peptides (NEPs)

Abstract: Successful host colonization by necrotrophic plant pathogens requires the induction of plant cell death to provide the nutrients needed for infection establishment and progression. We have cloned two genes encoding necrosis and ethylene-inducing peptides from Sclerotinia sclerotiorum, which we named SsNep1 and SsNep2. The peptides encoded by these genes induce necrosis when expressed transiently in tobacco leaves. SsNep1 is expressed at a very low level relative to SsNep2 during infection. The expression of Ss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
52
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(54 citation statements)
references
References 45 publications
(61 reference statements)
2
52
0
Order By: Relevance
“…Two S. sclerotiorum necrosis and ethylene-inducing protein (NEP) proteins (SsNEP1 and SsNEP2) were characterized by Bashi et al [30] and their necrosis-inducing activity demonstrated. In that study, both genes were induced at the mid to later times in the infection with SsNEP2 being expressed at much higher levels than SsNEP1 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Two S. sclerotiorum necrosis and ethylene-inducing protein (NEP) proteins (SsNEP1 and SsNEP2) were characterized by Bashi et al [30] and their necrosis-inducing activity demonstrated. In that study, both genes were induced at the mid to later times in the infection with SsNEP2 being expressed at much higher levels than SsNEP1 .…”
Section: Resultsmentioning
confidence: 99%
“…Host chemical defenses may be inactivated by inducible detoxification systems [28], while other proteins, such as SsPemG1 (protein elicitor from Magnaporthe grisea ), are recognized by the host and induce defenses [29]. SsNEP1 and SsNEP2 encode necrosis and ethylene-inducing like proteins (NLP), which induce necrosis in host tissues [30], as does cutinase [31]. A gene (SS1G_00263, ssv263) encoding a hypothetical protein with unknown mode of action is a virulence factor in S. sclerotiorum [32].…”
Section: Introductionmentioning
confidence: 99%
“…2009); an integrin-like protein, SSITL, that suppresses defense responses in Arabidopsis thaliana (although, in addition to the activity of SSITL in planta , deletion mutants for the cognate gene exhibited abnormal hyphal tip branching, slower growth in vitro and abnormally small sclerotia) (Zhu et al. 2013); two necrosis and ethylene-inducing proteins, SsNep1 and SsNep2, that cause necrosis when heterologously expressed in Nicotiana benthamiana (Dallal Bashi et al. 2010); a cutinase, SsCut, that causes cell death in a range of plant species, including the nonhost, wheat ( Triticum aestevum ) (Zhang et al.…”
Section: Introductionmentioning
confidence: 99%
“…SsNep2 expression is highly dependent on Ca 2+ concentration, and compounds increasing calcium levels (i.e. caffeine and lanthanum chloride) greatly reduced S. sclerotiorum virulence and expression of SsNep2 [52]. Thus, consistent with its putative role of intracellular calcium elevation, the haplotype 3 of HaRIC_B might be participating in the defense against SHR by repressing expression of the necrosis factor SsNep2 , through the de-regulation and elevation of cytosolic Ca 2+ concentrations in the target organ for pathogen attack.…”
Section: Discussionmentioning
confidence: 99%